Monoclonal antibody to a triggering structure expressed on rat natural killer cells and adherent lymphokine-activated killer cells (The Rockefeller University Press, 1989)
To study the cellular structures involved in NK and lymphokine- activated killer (LAK) cell function, we have produced a panel of mAbs that modulate the cytolytic function of a population of cells with LAK activity that derive from large granular lymphocyte (LGL)/NK cells (adherent LAK [A-LAK] cells). In this report, we describe an mAb (3.2.3; IgG1k) that recognizes a triggering structure that is expressed on rat LGL/NK cells and A-LAK cells. This epitope is also expressed on polymorphonuclear leukocytes (PMN). The expression of the epitope identified by mAb 3.2.3 increased progressively on A-LAK cells after culture in the presence of rIL-2. mAb 3.2.3 enhanced the cytolytic activity of NK and A-LAK cells against FcR+ target cells, but not FcR- target cells. However, this effect was not induced by F(ab')2 fragments of 3.2.3. This antibody also induced the release of N-alpha- benzyloxycarbonyl-L-lysine thiobenzy esteresterase by A-LAK cells. These data suggest that the epitope identified by mAb 3.2.3 is on a triggering structure expressed on rat NK cells and A-LAK cells. The expression of the epitope recognized by mAb 3.2.3 on LGL/NK cells and PMN suggests that this structure may be analogous to that identified by the anti-CD16 (-FcR) mAbs. However, the molecule immunoprecipitated by mAb 3.2.3 was a 60-kD dimer composed of two 30-kD chains. These data suggest that mAb 3.2.3 recognizes a unique triggering structure. As mAb 3.2.3 is the first antibody recognizing a determinant with functional significance, selectively expressed on both rat NK cells and A-LAK cells, it will be a useful tool for the study of NK cell ontogeny and function, and the development of cells with LAK activity from the NK cell compartment.